Exchange rate pass-through to Japanese prices: Import prices, producer prices, and the core CPI. (May 2022) - Sasaki, Yuri; Yoshida, Yushi; Otsubo, Piotr Kansho
Highlights: The ERPT to the consumer price level is negligible in the 1990 s and the early 2000 s. The ERPT still small but statistically significant after the global financial crisis. We construct effective exchange rate and producer price index at the industry level. The weakest link exists between the import price and domestic producer price. The within-industry effect between import and producer prices is not negligible. Abstract: Against the background of the two percent inflation target that Japan set in 2013, we investigate the impediments in the process of passing on exchange rate fluctuations to the core consumer price index. To this end, we construct the industry-level nominal effective exchange rate and industry-level producer price indices, which are matched with the industry classifications used for import price indices. Time-varying parameter vector autoregression analysis reveals that, in general, exchange rate pass-throughs increased, especially after the global financial crisis. Among the pass-throughs that occur at each stage of the import price, domestic producer price, and consumer price, we find that the weakest link exists between the import price and domestic producer price. However, the impact on the within-industry effect is not negligible; the small spillover effect on other industries at the producer price stage prevents consumer prices from rising after depreciation.